Oral hyperpigmentation as adverse effect to capecitabine - Silva, Paula Verona Ragusa; Chicrala, Gabriela Moura; Soares-Junior, Luiz Alberto Valente; Dias, Rafael Rodrigues; Santos, Paulo Sérgio Silva (Journal of Oral Diagnosis, 2017)
Capecitabine (Xeloda®) is an antineoplastic drug normally used as adjuvant chemotherapy for metastatic colorectal and breast cancer. A common adverse effect of capecitabine is hand and foot syndrome (HFS), a condition that, although not life threatening, can reduce drastically quality of life and result in patient withdrawal from treatment. Palmoplan- tar hyperpigmentation is a condition that has been found as the initial manifestation of HFS in most patients. The association of palmoplantar and oral hyperpigmentation as an adverse effect to capecitabine has rarely been described in the literature. We report a case of oral and palmoplantar hyperpigmentation in a 61-year-old woman receiving ca- pecitabine for metastatic colon cancer. At the chemotherapy 2nd cycle, the patient referred burning mouth, and clinical inspection revealed brownish spots measuring between 2 and 10 mm, in addition to similar hyperpigmentated macules in palms and soles of feet, both asymptomatic. A 7-month-follow-up, still under chemotherapy with oral Xeloda®, showed regression of mouth manifestations while the palmoplantar spots intensified, with progression of dryness and tingling. This report highlights the importance of early diagnosis of HFS through the oral hyperpigmentation, which is a manifestation easily detectable by the dentist.